(untitled) (Historia, 2021)
Neither by accident nor design, Natal became home to over 50 000 Indian immigrants during the latter half of the nineteenth century. At the request of fewer than 50 sugar planters, colonial Natal embarked on a labour dispensation which was initially envisaged as "an experiment," on a small scale, as Governor John Scott saw it. Appreciated for their contribution as labourers to the success of sugar production, Indians nonetheless, were resented by white colonists as settlers after they had completed their indenture contracts. That resentment was heightened by the influx of traders and non-indentured Indians into Natal after 1875 and found expression in published opinion and in discriminatory legislation. By the 1890s Natal’s anti-Indian legislation became an imperial controversy which also proved life-changing for M.K. Gandhi. This article attempts to track the evolution of white settler attitudes to what was termed the "coolie curse." Gedurende die tweede helfte van die negentiende eeu het Natal die tuiste van meer as 50 000 Indiese immigrante geword. Op versoek van minder as 50 suikerboere het koloniale Natal begin met ’n arbeidsbedeling wat aldus die mening van Goewerneur John Scott slegs as ’n "kleinskaalse eksperiment" beskou was. Nieteenstaande die waardering vir hulle bydrae as arbeiders tot die sukses van suikerproduksie, was blanke koloniste nogtans verbitterd teenoor Indiers as setlaars nadat hulle inboekstelsel kontrakte verstryk het. Hierdie misnoë was verder aangevuur deur die instroming van handelaars en ongekontrakteerde Indiers in Natal na 1875, en was ook duidelik verwoord in gepubliseerde opinie asook diskriminerende wetgewing. Teen die 1890s het Natal se anti-Indier wetgewing ontaard in ’n imperiale kontroversie wat selfs die toekoms van M.K. Ghandi beinvloed het. Hierdie artikel poog om die evolusie van blanke setlaars se houding ten opsigte van die destydse sogenaamde "coolie curse" te ontleed.